Q07 Long-term safety and tolerability of pridopidine in patients with huntington's disease (HD): results of the mermaihd study open-label extension. (29th August 2012) - Squitieri, F; Landwehrmeyer, B; Reilmann, R; Rosser, A; Garcia de Yebenes, J; Prang, A; Ivkovic, J
Abstract : Background: The MermaiHD study was a 6-month randomised placebo-controlled trial (RCT) examining the efficacy and safety of pridopidine (Huntexil®, NeuroSearch A/S, Ballerup, Denmark) in patients with HD. Aims: To perform a 6-month open-label extension (OLE) to the RCT, to assess the long-term safety and tolerability of pridopidine. Methods: OLE eligible patients must have completed the RCT on treatment (placebo, pridopidine 45 or 90 mg/day). All OLE patients received pridopidine 45 mg/day (weeks 1–4) then 90 mg/day (weeks 5–22). Exposure, AEs, withdrawals, dose de-escalation, vital signs, electrocardiogram data and laboratory parameters were recorded. Results: Similar numbers from each RCT group entered the OLE (n=113, 125 and 115 for placebo, 45 mg/day and 90 mg/day), of whom 86% completed the OLE. RCT baseline demographics (gender, race, age, height, weight and BMI) were similar between patients who did/did not enter the OLE, whereas treatment-emergent AEs were more common in those who did not enter (includes placebo group). Over the course of both studies, similar percentages from each group reported ≥1 AE and ≥1 SAE (80%, 81%, 83%; and 8%, 13%, 9%; for placebo, 45 mg/day and 90 mg/day) The AE profile during both studies was similar, with falls and worsening of chorea most common. In the OLE, the proportion of patients reporting ≥1 AE was higher in those who received pridopidine in the RCT than received placebo (68% vs 57%). Worsening of chorea was more common in patients who received pridopidine in the RCT than received placebo (12.5% vs 6.2%), although in 9/30 pridopidine patients, worsening occurred after treatment discontinuation. After 52 weeks of treatment, no clinically meaningful effects or safety concerns were identified for laboratory parameters and electrocardiogram results. In the first 12 weeks of the RCT, a small but transitory increase in heart rate occurred in patients on pridopidine. Conclusions: Pridopidine (up to 90 mg/day) has a good safety profile and is well tolerated, for up to 1 year of treatment.